PEMAKAIAN GOROAWASE DALAM BAHASA JEPANG - KHAIRA IMANDIENA BAHALWAN (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2018)
In Japanese language, the term goroawase is known as a word play that uses numbers. The use of goroawase in Japanese varies greatly. In this article we can see 7 (seven) types of goroawase that are used in Japanese media, (1) as word play, (2) as an abbreviation, (3) as superstition, (4) as the arrangement of celebration day's names, (5) as a way to memorize telephone numbers, (6) as a way of memorize historic years and dates, and (7) as a way of memorize scientific numbers. Keywords: Goroawase, word play, memorize technique